Applied e-learning and e-teaching in higher education [ - Donnelly, Roisin; McSweeney, Fiona (Information Science Reference, 2009)
"This book presents international practices in the development and use of applied e-Learning and e-Teaching in the classroom in order to enhance student experience, add value to teaching practices, and illuminate best practices in the area of e-Assessme